My life so far - Fonda, Jane (New York Random House, 2005)
Jane Fonda divides her "life so far" into three "acts," writing about her childhood, first films, and marriage to Roger Vadim in Act One. These early years are marked by profound sadness: her mother's mental illness and suicide when Jane is twelve years old, her father's emotional distance, and her personal struggle to find her way in the world. By her second act, she lays the foundation for her activism, even as her career takes flight. She highlights her struggle to live consciously and authentically while remaining in the public eye as she recounts her marriages to Tom Hayden and Ted Turner, and examines her controversial and defining involvement with the Vietnam War. As her film career grows, Fonda learns to incorporate her roles into a larger vision of what matters most in her life. In her third act, she is prepared to do the work of a lifetime--to begin living consciously in a way that might inspire others who can learn from her experiences. provided by the publisher.
7/05
Keywords: Fonda, Jane -- autobiography; Motion pictures actors and actresses -- Biography -- United States